Supersensitive Multifluorophore RNA‐FISH for Early Virus Detection and Flow‐FISH by Using Click Chemistry. (20th April 2020) - Raddaoui, Nada; Croce, Stefano; Geiger, Florian; Borodavka, Alexander; Möckl, Leonhard; Stazzoni, Samuele; Viverge, Bastien; Bräuchle, Christoph; Frischmuth, Thomas; Engelke, Hanna; Carell, Thomas
Abstract: The reliable detection of transcription events through the quantification of the corresponding mRNA is of paramount importance for the diagnostics of infections and diseases. The quantification and localization analysis of the transcripts of a particular gene allows disease states to be characterized more directly compared to an analysis on the transcriptome wide level. This is particularly needed for the early detection of virus infections as now required for emergent viral diseases, e. g. Covid‐19. In situ mRNA analysis, however, is a formidable challenge and currently performed with sets of single‐fluorophore‐containing oligonucleotide probes that hybridize to the mRNA in question. Often a large number of probe strands (>30) are required to get a reliable signal. The more oligonucleotide probes are used, however, the higher the potential off‐target binding effects that create background noise. Here, we used click chemistry and alkyne‐modified DNA oligonucleotides to prepare multiple‐fluorophore‐containing probes. We found that these multiple‐dye probes allow reliable detection and direct visualization of mRNA with only a very small number (5–10) of probe strands. The new method enabled the in situ detection of viral transcripts as early as 4 hours after infection. Abstract : More is less ! Increasing the number of fluorophores per oligonucleotide probe allows superb sensitivity, as the fewer the number of probes needed, the lower the background noise. With just a small number of triply labeled strands, RNA‐FISH‐based detection of RNA transcripts was possible in live cells, and a virus could be detected after only 4 hours.